The pleiotropic roles of circular and long noncoding RNAs in cutaneous melanoma. Issue 3 (18th June 2021) - Montico, Barbara; Giurato, Giorgio; Pecoraro, Giovanni; Salvati, Annamaria; Covre, Alessia; Colizzi, Francesca; Steffan, Agostino; Weisz, Alessandro; Maio, Michele; Sigalotti, Luca; Fratta, Elisabetta
Abstract : Cutaneous melanoma (CM) is a very aggressive disease, often characterized by unresponsiveness to conventional therapies and high mortality rates worldwide. The identification of the activating BRAF V600 mutations in approximately 50% of CM patients has recently fueled the development of novel small‐molecule inhibitors that specifically target BRAF V600 ‐mutant CM. In addition, a major progress in CM treatment has been made by monoclonal antibodies that regulate the immune checkpoint inhibitors. However, although target‐based therapies and immunotherapeutic strategies have yielded promising results, CM treatment remains a major challenge. In the last decade, accumulating evidence points to the aberrant expression of different types of noncoding RNAs (ncRNAs) in CM. While studies on microRNAs have grown exponentially leading to significant insights on CM biology, the role of circular RNAs (circRNAs) and long noncoding RNAs (lncRNAs) in this tumor is less understood, and much remains to be discovered. Here, we summarize and critically review the available evidence on the molecular functions of circRNAs and lncRNAs in BRAF V600 ‐mutant CM and CM immunogenicity, providing recent updates on their functional role in targeted therapy and immunotherapy resistance. In addition, we also include an evaluation of several algorithms and databases for prediction and validation of circRNA and lncRNA functional interactions. Abstract : In the last decade, accumulating evidence points to the aberrant expression of different types of noncoding RNAs in cutaneous melanoma (CM). Here, we summarize and critically review the available evidence on the molecular functions of circular RNAs (circRNAs) and long noncoding RNAs (lncRNAs) in BRAF V600 ‐mutant CM and CM immunogenicity, providing recent updates on their functional role in targeted therapy and immunotherapy resistance. In addition, we also include an evaluation of several algorithms and databases for prediction and validation of circRNA and lncRNA functional interactions.